How to Overcome the Barriers Between Economy and Sociology With Open Innovation, Open Evaluation and Crowdfunding? - Freund, Robert (International Journal of Industrial Engineering and Management, 2010)
This paper is structured in the following way. The first part describes Open Innovation as a business model which uses internal and external knowledge for innovation. Part two focus on the large base of ideas which can be evaluated (intern/extern) with IT-solutions (Open Evaluation). And in part three it is argued, that crowdfunding can overcome the barriers between economy and sociology. Article history: Received (10.07.2010); Revised (19.09.2010); Accepted (30.09.2010)